Factors that influence Muslim's intention to purchase non-Muslim's halal food in Kangar / Hanif Omar Baki - Omar Baki, Hanif (2017)
To investigate the determinant factors that consumers may consider in buying Halal food produced by non-Muslim manufacturers in Kangar area. A field survey carried out with the help of a questionnaire constructed by using a modified Likert-scale. A total of 50 set of questionnaires were distributed randomly in Kangar area and receive also 50 completed replies. Multiple regression analysis assessed the three determinant factors towards Muslim’s purchase intention. The three variables have significant effect and predict a good proportion of the variance in Muslim’s purchase intention. The research results indicate that the product ingredient, halal awareness and Islamic brand can positively and significantly affect the Muslim’s purchase intention on Non-Muslim’s Halal food manufacturer. The relationships investigated in this study deserve more effort on understanding Muslim’s buying behaviour. This is because the data analysed were collected from one area only in this country. More studies are required before general conclusion can be drawn. This study has practical significance for non Muslim’s Halal packaged food manufacturer for understanding the buying behaviour of Muslim consumers and using them for effectively positioning the purchase intention of their food product.